2017
DOI: 10.1021/acs.nanolett.7b02787
|View full text |Cite
|
Sign up to set email alerts
|

pH-Driven Reversible Self-Assembly of Micron-Scale DNA Scaffolds

Abstract: Inspired by cytoskeletal scaffolds that sense and respond dynamically to environmental changes and chemical inputs with a unique capacity for reconfiguration, we propose a strategy that allows the dynamic and reversible control of the growth and breakage of micronscale synthetic DNA structures upon pH changes. We do so by rationally designing a pH-responsive system composed of synthetic DNA strands that act as pH sensors, regulators, and structural elements. Sensor strands can dynamically respond to pH changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
112
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(112 citation statements)
references
References 38 publications
0
112
0
Order By: Relevance
“…To ensure thermal stability at 37°C, these nanotubes were designed with longer sticky ends than previously developed versions (Figure 1A ) ( 1 ). The nanotubes also contained a single-stranded overhang on strand 2 of the DNA tiles for use with another project relating to dynamic activation and deactivation of tiles ( 59 ). We also found that the single-stranded overhang domain aided in the efficient assembly of nanotubes in transcription buffer ( Supplementary Figure S1 and SI Section 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…To ensure thermal stability at 37°C, these nanotubes were designed with longer sticky ends than previously developed versions (Figure 1A ) ( 1 ). The nanotubes also contained a single-stranded overhang on strand 2 of the DNA tiles for use with another project relating to dynamic activation and deactivation of tiles ( 59 ). We also found that the single-stranded overhang domain aided in the efficient assembly of nanotubes in transcription buffer ( Supplementary Figure S1 and SI Section 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Over the past three decades,great progress has been made in dynamic DNAn anotechnology toward the enrichment of regulation toolboxes and the exploration of new functions and applications. [1] pH-triggering is one of the most widely used strategies in these pursuits,b yw hich various dynamic DNA systems have been demonstrated, including DNAmachines, [2] sol-gel transition, [3] pH-triggered assembly, [4] cellular pH mapping, [5] switchable catalysis, [6] controlled release. [7] Most of these reports take advantage of the pH switchable behaviors of specific DNAs equences,s uch as i-motif and A-motif,a sw ell as triplex structures to realize the structural controls.While these designs are ingenious,they are restricted by the limited availability of special DNAs equences.I f as equence-independent method could be developed to deliver am ore universal and versatile platform to regulate DNAs elf-assembly by pH, it would greatly broaden the potential of dynamic DNAn anotechnology.H owever, such astrategy has not yet been reported.…”
mentioning
confidence: 99%
“…More recently,t he triplex and i-motif units have been incorporated in more complicated, highero rdered DNA architectures, such as nanocages, nanotubules, DNA origami,a nd even macroscopic crystals. [26][27][28][29] Mao and co-workersd eveloped as trategy to reversibly control the assembly and disassembly of aD NA nanocage by incorporating pH-sensitive triplex parts into the sticky end re-gions of the component tiles formingt he nanocages (i.e.,t etrahedrons). [26] When the solution was slightly basic (pH 8.0), the tripletsd issociated owing to ad eprotonation of Cb ases, resultingi nd isassembled DNA tetrahedrons.…”
Section: Category 1: Protonationo Fnucleobasesmentioning
confidence: 99%
“…Ricci and co-workerse mployedapHsensitivet riplex structure to lock and unlock ar egulator strand,w hich determined the formationa nd breakage of a micron-sized DNA nanotube. [27] Willner and Wu achieved reversible associations of hexagonalD NA origami units by controlling the bridging of origami framesw ith pH-responsive triplex and i-motif moieties (Figure2b). [28] Normally,w eak inter-unit interactions are critical during DNA assemblyt oa llow for as elf-correction mechanism that favors large, well-ordered DNA assemblies (e.g.,c rystals).…”
Section: Category 1: Protonationo Fnucleobasesmentioning
confidence: 99%